Casos notificados de leptospirose relacionados à precipitação mensal na cidade de Belém - Pará - ASSIS, Leandro Michell Moraes de (2019)
Belém is a city with high total annual rainfall, coupled with poor health administration, it becomes a city susceptible to outbreaks of waterborne diseases, especially leptospirosis, issue focus of this work. Using statistical methods applied to a date series of eleven years (1999-2009), we analyzed the possible relationship between the reported cases of leptospirosis and the monthly distribution of rainfall. The results indicated a good relationship between the variables being studied, and precipitation for determining currencies of leptospirosis, which in the rainy season the highest values ware observed in this disease.